A comparative study and evaluation of ERP reference models in the context of ERP IT-driven implementation: SAP ERP as a case study. Issue 4 (2nd July 2018) - Al-Sabri, Hamdan Mohammed; Al-Mashari, Majed; Chikh, Azeddine
Abstract : Purpose: The purpose of this paper is to consider the question of what is an appropriate enterprise resource planning (ERP) reference model for specifying areas of change in the context of IT-driven ERP implementation and through the model matching. There are other implicit goals to increasing the awareness of the reference models, as this highlights the principles embedded in ERP systems and explains the classification of reference models, which is useful in terms of the reuse of knowledge. Design/methodology/approach: In this paper, a comparison between ERP reference models is conducted using a suitable decision-making technique and the final results are discussed. The comparison depends on nine criteria related to conceptual ERP reference models: scope, abstraction, granularity, views, purpose, simplicity, availability, ease of use for model matching, and target audience. Findings: This study concludes that the business process reference model is best for specifying areas of change in the context of IT-driven ERP implementations. The final ranking of the alternatives based on all criteria places the system organizational model second, followed by the function and data/object reference models, in that order. Originality/value: This paper is one of very few studies on the selection of appropriate ERP reference models according to the ERP implementation approach and model matching factors. This research also provides an in-depth analysis of various ERP reference model types.